What I live now darkness is similar to night...: Youth as a model of strangeness in the work of Jiří Karásek ze Lvovic - Kolařík, Karel (Bohemica Olomucensia, 2012)
The study analyzes the character of a youth in the work of Jiří Karásek ze Lvovic. It points at Mácha's exposition (from The Night at Bezděz) as its possible inspiration and incorporates findings in the context of visual arts of the era (using namely the work of Jan Preisler). Karásek conceives a youth as a stranger, a being that is excluded from the society, and uses youth's androgyny as the symbol of the exclusion.